The Human Genome Project - Toriello, James (New York : Rosen Pub. Group, 2003)
Describes potential uses for the ten-year, multimillion dollar Human Genome Project and its process of gene mapping; includes web citation for an interactive map of chromosomes.
Includes bibliographical references and index
Keywords: Human Genome Project; Human Genome Project; Gene mapping; Medicine; Genetics